2017
DOI: 10.1103/physrevb.95.184514
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in noncentrosymmetric Ag2Pd3S

Abstract: We have successfully synthesized the single crystal of Ag 2 Pd 3 S, which exhibits superconductivity with the transition temperature of T c = 2.25 K. Ag 2 Pd 3 S crystallizes in the space group P 4 1 32 with the filled β-Mn structure, which has no inversion symmetry. The value of the Ginzburg-Landau parameter κ GL indicates that Ag 2 Pd 3 S is a type-II superconductor. C(T c )/γ n T c = 1.50 and 2 /k B T c = 3.48 from the heat-capacity analyses indicate that Ag 2 Pd 3 S is a weak-coupling Bardeen-Cooper-Schrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…In the present work, strontium Rydberg atoms are created in a tightly-collimated beam through laser-induced multiphoton excitation. The (crossed) laser beams employed are tightly focused to define a small excitation volume whose linear dimensions, ∼ 50µm, are less than the blockade radius, R b ∼ 100µm at n ∼ 300 [25]. Production of a Rydberg atom in this volume thus suppresses further excitation until the atom has traveled ∼ 100µm in the beam direction which, given the mean velocity of atoms in the strontium beam,v ∼ 4 × 10 2 m s −1 , typically requires ∼ 250 ns.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present work, strontium Rydberg atoms are created in a tightly-collimated beam through laser-induced multiphoton excitation. The (crossed) laser beams employed are tightly focused to define a small excitation volume whose linear dimensions, ∼ 50µm, are less than the blockade radius, R b ∼ 100µm at n ∼ 300 [25]. Production of a Rydberg atom in this volume thus suppresses further excitation until the atom has traveled ∼ 100µm in the beam direction which, given the mean velocity of atoms in the strontium beam,v ∼ 4 × 10 2 m s −1 , typically requires ∼ 250 ns.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Recent work [24,25] in this laboratory has shown that even at very-high-n, n ≥ 300, it is possible to observe dipole blockade in a hot strontium atomic beam by using tightly-focused laser beams to create a localized excitation volume and that the blockade radius is large, ∼ 100µm. Such blockade can be exploited to generate a string of Rydberg atoms (see Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One remarkable observation in strongly interacting systems is the reduction of the classification of topological phases in the presence of correlations; the classification of topological phases changes due to strong correlations [10][11][12][13] . Other interesting examples are socalled topological Kondo insulators [14][15][16][17][18][19] , which are topologically nontrivial f -electron materials including strong correlations in the f -orbital.…”
Section: Introductionmentioning
confidence: 99%
“…Second, this gate set allows certain transversal implementations of fault-tolerant universal quantum computation using topological error correction codes. Transversality means that, in order to perform gates on the encoded logical qubits, one can apply corresponding gates to the physical qubits in a parallel fashion, and this convenience has sparked recent interest on this gate set [9][10][11][12][13][14]. Third, the manybody entangled states generated by the CCZ gates are known as hypergraph states in entanglement theory [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%